Emotional competences training in equestrian sport – a preliminary study. Issue 4 (4th July 2021) - Schütz, Kathrin; Rahders, Felicitas; Mosley, Emma; Laborde, Sylvain
ABSTRACT: The aim of this study was to assess the effects of an emotional competences (EC) training with domestic horses on equestrianś trait EC. To this end, an experimental group ( n = 26) received a specific EC training intervention with horses as medium (in group format), whereas the control group ( n = 25) did not receive any training. The intervention consisted of two group sessions with horses for a duration of six hours and of nine hours of homework practicing the exercises with horses (over a period of four weeks). EC were measured with the Profile of Emotional Competences in both groups using a pre–post-test-design. Results reveal that the level of EC increased significantly in the intervention group when compared to the control group. This outcome suggests the possibility of improving trait EI in humans through equine-assisted exercises.